Paediatric rhabdomyosarcoma: MyoD1 demonstration in routinely processed tissue sections using wet heat pretreatment (pressure cooking) for antigen retrieval. Issue 1 (January 1997) - Engel, M E; Mouton, S C; Emms, M
Abstract : AIMS: To investigate wet heat pretreatment (pressure cooking) as a means of antigen retrieval for demonstration of MyoD1 in paraffin wax embedded tissue. METHODS: Routinely processed tissue sections of transmission electron microscope confirmed cases of rhabdomyosarcoma were stained immunohistochemically with the MyoD1 antibody. Antigen retrieval was achieved by wet heat pretreatment of the tissue sections. RESULTS: MyoD1 was stained successfully in all seven cases. The protein was localised to nuclei and cytoplasm depending on the type of tumour cell. CONCLUSIONS: Wet heat pretreatment for antigen retrieval from routinely processed tissue sections permits excellent subsequent immunostaining for MyoD1 in rhabdomyoblasts.